Discrete lot sizing and scheduling on parallel machines: description of a column generation approach - Duarte, António J.S.T. (2014)
In this work, we study the discrete lot sizing and scheduling problem (DSLP) in identical parallel resources with (sequence-independent) setup costs and inventory holding costs. We propose a Dantzig-Wolfe decomposition of a known formulation and describe a branch-and-price and column generation procedure to solve the problem to optimality. Preliminary results show that the lower bounds provided by the reformulated model are stronger than the lower bounds provided by the linear programming relaxation of the original model.